Pevatrons dentro da galáxia: identificação e mecanismos de aceleração - Götz, Débora Beatriz (2023)
Cosmic rays are charged particles propagating through space and reaching Earth with different energies, reaching up to 1020 eV. The particle sources have not yet been identified, and they can be outside the Galaxy or inside the Galaxy. In this dissertation, the cosmic rays coming from inside the galaxy are studied. One of the possible sources of cosmic rays that reach Earth with energy in the order of PeV (1015 eV) is the só-called PeVatron. Near the galactic center, it was detected by Observatories charged particles that evidence a population of PeVatrons in the region, such as proton detection with 0.04 PeV and photons with 1.4 PeV. Using the GALPROP software to resolve galactic cosmic ray emission, simulations were performed with pulsars from this population of PeVatrons as cosmic ray sources. The outcomes comprise fluxes of cosmic rays and their secondary particles, particularly gamma rays. These were juxtaposed with data provided by observatories. The discussions indicate that these PeVatrons are indeed high-energy sources. Moreover, they suggest that gamma rays resulting from the propagation of cosmic rays can account for a segment of the observed gamma radiation.